Distance learning for teaching in physical education - Silva, Regina Celia A. [UNESP]; e Silva, Vera Lucia de F.F. [UNESP]; Silva, André Pontes (FapUNIFESP (SciELO), 2019)
— Aims: The objective of this article is to show, by analyzing the curricula of the professional formation in Physical Education, that it is possible the formation of teachers in Distance Learning Physical Education courses since the act of reflecting before, during and after the pedagogical practice characterizes the quality of contemporary educational development. A qualitative research; the present study consists of an analysis of curricula and Professional Training of Distance Learning in Physical Education, subsidized in bibliographic research. As the traditional teaching model prioritizes the selection of the most skilled in the search for the hero athlete, the pedagogical proposal based on reflection is more interesting since not all students will be or wish to be athletes. In this way, distance learning for teaching in physical education seems to be an excellent educational strategy for our postmodern society.
Keywords: Distance education; Education; Physical education; Physical education professional; Teachers formation